2015
DOI: 10.1016/j.jalgebra.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Braid groups of imprimitive complex reflection groups

Abstract: We obtain new presentations for the imprimitive complex reflection groups of type $(de,e,r)$ and their braid groups $B(de,e,r)$ for $d,r \ge 2$. Diagrams for these presentations are proposed. The presentations have much in common with Coxeter presentations of real reflection groups. They are positive and homogeneous, and give rise to quasi-Garside structures. Diagram automorphisms correspond to group automorphisms. The new presentation shows how the braid group $B(de,e,r)$ is a semidirect product of the braid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…The last fact can also be proved group theoretically ( [15]). The Artin groups corresponding to the finite complex reflection groups G(de, e, r) is torsion free, since A G(de,e,r) is a subgroup of A Br ([ [7], Proposition 4.1]).…”
Section: Pa=pure Artin Group Of Typementioning
confidence: 99%
See 2 more Smart Citations
“…The last fact can also be proved group theoretically ( [15]). The Artin groups corresponding to the finite complex reflection groups G(de, e, r) is torsion free, since A G(de,e,r) is a subgroup of A Br ([ [7], Proposition 4.1]).…”
Section: Pa=pure Artin Group Of Typementioning
confidence: 99%
“…For the proof of the theorem in the G(de, e, r)-case we refer to Remark 2.1. In ([ [7], Proposition 4.1]) it is shown that A G(de,e,r) is a subgroup of A Br . (In [7], these are called braid groups associated to the reflection groups).…”
Section: Proofs Of the Theoremsmentioning
confidence: 99%
See 1 more Smart Citation
“…This section sets the stage for our later work by establishing a set of geodesic normal forms for the complex reflection groups G(de, e, n), using the generating sets introduced by Corran-Picantin [10] and Corran-Lee-Lee [9] for G(e, e, n) and G(de, e, n) for d > 1, respectively. The case of G(e, e, n) has been already done in our previous work (see Section 3 of [17]).…”
Section: Definitions and Preliminariesmentioning
confidence: 99%
“…In order to establish these bases, our attention is firstly shifted to the complex reflection groups G(de, e, n). We construct geodesic normal forms for these groups by using the presentations of Corran-Picantin [10] and Corran-Lee-Lee [9] of G(e, e, n) and G(de, e, n) for d > 1, respectively. The geodesic normal forms are very natural and easy to describe.…”
Section: Introductionmentioning
confidence: 99%